Finding Tessa [large type] - Hendricks, Jaime Lynn (Center Point Large Print, 2021)
"When Jace Montgomery comes home late from entertaining clients, he discovers that his wife Tessa is missing. There's broken glass below the kitchen window. Clumps of her hair. Blood. The cops in their small New Jersey town have him pegged as a suspect, especially after he explodes at a reporter during a press conference. Jace maintains his innocence despite the mounting evidence against him, but when a coworker he's accused of having an affair with also disappears and a search warrant turns up an illegal gun in Jace's home, all signs point to him as the culprit. What is he really hiding? Meanwhile, Tessa finally feels safe, having set up her husband to take the fall for her disappearance - and someone close to him is helping her put him away. Breaking her lifelong pattern of bad men is only one hurdle she has to overcome. The other is outrunning her secret past while trying to stay alive, especially when those in her new life aren't who they appear to be. Jace's explanation doesn't add up and the authorities are closing in. Will Tessa's old life catch up to her and drag her back to a life of abuse before justice is served?"--